Anemia Prevention in Adolescent Females With Lawrence W. Green Theory Approach: A Literature Review - Ismail, Mujiono; Aisah, Siti; Soesanto, Edy; Pranata, Satriya (Babali Publisher, 2025)
Background: The prevalence of anemia worldwide is very high, particularly in developing countries, including Indonesia. Adolescent girls are especially susceptible to anemia, with the monthly menstrual cycle being one of the contributing factors. This review aims to synthesize data by analyzing several articles that focus on the prevention of anemia in adolescent girls using the Lawrence W. Green theory approach. Methods: The method used for this article is a literature review of articles published between 2020 and 2024. The sources include Google Scholar, PubMed, and ScienceDirect, with the keywords